Inequality in Brazil from 2016 to 2017: A decomposition exercise and labor market analysis of virtually no change (which is good news) - Sergei Soares (Institute for Applied Economic Research (ipea), 2018)
This article uses recently released data from the Pesquisa Nacional por Amostra de Domicílios Contínua (PNAD Contínua), Brazilian household survey to calculate changes in inequality as measured by the Gini coefficient from 2016 to 2017. A Shorrocks decomposition by factor components is also undertaken, as well as a limited analysis of the wage inequality and the labor market contribution to household inequality. The main results are: i) the Gini coefficient fell 0.18 point from 2016 to 2017, going from 54.1 to 53.8, which is a very small reduction in inequality; ii) this reduction is due to the interplay between labor and social protection incomes; and iii) the labor market by itself is playing against reductions in inequality, which shows the relevance of the (still limited and not very progressive) Brazilian social protection system
Keywords: D31; D33; 330; inequality in Brazil; Gini coefficient; Shorrocks decomposition; concentration coefficient